Not only the poor! A closer look at regional differences in Italian emigration (1946-2019) - Traci Michelle Ricciardo (The Journal of European Economic History (JEEH), 2024)
Although much research on migration has been carried out over the years, the focus of the attention has been mostly on immigration and its effects on the host countries and the economic drivers for choosing migration. Italian emigration abroad in post-World War II (1946-73) and in the 21st century (2004-19) forms a key part of Italy's recent history. Converging and diverging trends in Italian emigration have not received enough attention in literature to date. The aim of this study is to compare the two periods of mass emigration, highlighting differences and similarities by analysing the emigration trends from the various Italian Regions, using percentage values, as opposed to absolute values, which can often distort the true picture. The study provides a historical overview of the changes in Italian emigration on both the macro-area and regional levels. The use of secondary literature and data allowed for an analysis between the different regional origins of the migrants and the emigration trends in the regions, as well as for the formulation of hypotheses regarding the emigrants' migration motives. This research helps fill the gap in literature through the comparison of the 1946-1973 and 2004-2019 periods of Italian mass emigration. The findings reveal the scale of this emigration, the various regional origins of the emigrants, the regional differences in the trends, the attitude to emigration in sender societies and also the potential reasons behind the emigrants' departure. Results provide enough information to affirm that today Italian emigration is due to the increased movements of people in a globally interconnected labour market, but, unlike the 1946-1973 mass migration, it pertains mainly to higher-income Italian regions, highlighting the importance of the need to look beyond the purely economic drivers and determinants to better understand the reasons behind the choice to emigrate.
Keywords: 330; Emigration; Migrants; Region; Italy; Auswanderung; Migranten; Region; Italien